Spatial distribution and risk assessment of heavy metals in seawater and sediments in Jieshi Bay, Shanwei, China - Zhou, Wen; Cao, Qian; Hong, Man; Lei, Yutao; Wen, Ding; Zhang, Dengfeng (Frontiers in Marine Science, 2022)
The industrialization of 20th century in China brought on rapid urbanization, resulting in a series of serve environmental problems. Heavy metal, as an indicator of coastal contamination, is analyzed to assess the risk in the study area. In this study, the characteristics of 6 heavy metals in surface seawater, sediments, and marine organisms are explored using pollution assessment, partitioning and bioaccumulation, and ecological risk assessment. The results showed Hg, Pb, and Zn were the major risk factors for seawater which are potentially correlated with human activities when the sediments were mainly influenced by Hg and Zn. And Cd and As could share the common source of the pollutants. And Cd and As could share the common source of the pollutants. Meanwhile, with the better quality of marine life, local species are more sensitive to Cu, Hg, and Cd. Based on the analysis of spatial distribution and risk assessment, the heavy metals have not caused a serve environmental problem in the study area, but potential pollution of HMs should still be attention to the decision makers.